Prevelance, risk factors and adverse perinatal outcomes of bacterial vaginosis in pregnancy - Shetty, Prasanna Kumar; Menon, Akhila G.; Rai, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Bacterial Vaginosis (BV) is the most common lower genital tract syndrome in women of age group 16 to 25years.BV is a disorder of the vaginal microbial ecosystem characterized by a shift in the vaginal flora, from the normally predominant Lactobacillus species to one dominated by a mixed flora. The prevalence of BV can be around 15-30% and upto 50% in pregnancy. This study aims to study the prevalence of BV and their adverse outcomes on pregnancy. Methods: It is a Cross Sectional Study at Department of Obstetrics and Gynecology, at a tertiary care hospital, for a period of one and half year from November 2016-April 2018.Pregnant women attending antenatal clinic were enrolled after obtaining an informed consent and vaginal swab examination done. The sample size was 200. Results: The prevalence of BV in pregnant females was 18%. The major risk factors for BV in pregnancy were young age, low socioeconomic status and recent sexual activity. All patients who took treatment for BV had good outcome. Amsel criteria had low sensitivity but very high specificity(95%).Individually vaginal PH had a very high sensitivity(91.6%) when compared to the gold standard Gram stain. Conclusions: Routine screening is recommended for all pregnant women with risk factors and with symptoms. Early diagnosis and treatment in pregnant women who are asymptomatic and with no risk factors can prevent adverse outcome.